How NHS data could benefit us all and how to build the trust needed to make it happen - O'Brien,N; Ghafur,S; Howitt,P; O'Shaughnessy,J; Darzi,A (British Journal of Hospital Medicine, 2023)
The pandemic has accelerated the data-sharing conversation and patients are increasingly receptive to sharing data, but missteps in this area could undermine public trust. This article outlines public concerns, lessons learned from previous unsuccessful activities, and the potential for secure data environments, which will be vital for the UK to maximise benefits for patients and the NHS.